2015
DOI: 10.1186/s40807-015-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of biogas using small-scale plug flow reactor and sizing calculation for biodegradable solid waste

Abstract: Experiment was conducted on the fabricated biodigester of capacity 30 l. Slurry of cow manure in water was fed through the inlet until the digester is about 80% filled with slurry, and the slurry surface on both inlet and outlet did not leave holes by which the air can get into the digester. This was to ensure the anaerobic condition in the gas space inside the digester. After the first filling, both the inlet and outlet were covered and gas valve to the gas holder was opened. In the first 20 days, the gas hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Other developed member states are also unwilling to increase costs associated with sharing such technologies [120]. On the other hand, EU member states that spend a lot less money on the research and development of renewable energy sources argue that the cost associated with intellectual property rights should be shared amongst all member states [121].…”
Section: Technology Transfer and Ipr Challengesmentioning
confidence: 99%
“…Other developed member states are also unwilling to increase costs associated with sharing such technologies [120]. On the other hand, EU member states that spend a lot less money on the research and development of renewable energy sources argue that the cost associated with intellectual property rights should be shared amongst all member states [121].…”
Section: Technology Transfer and Ipr Challengesmentioning
confidence: 99%
“…Over a period of one year, bio-methane production from a raw septic tank sludge in a 2 m 3 pilot reactor was investigated, showing that methane concentration increased from 73.15-81.83% upon sonication pretreatment of the sludge [22]. Warade et al [23] designed a portable bioreactor having 35 l working volume for producing biogas from Napier grass along with cow dung at an operating temperature range from 20 to 32 o C. They reported that the biogas production reached as high as 0.44 m 3 /kg VS. By using a compact plug ow reactor, Ramaswamy and Vemareddy [24] could produce biogas from cow dung and water in ratio of 1:10, which was enough to cook three meals a day for a family of six. Zeng et al [25] constructed a self-otation bioreactor and investigated its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Over a period of one year, bio-methane production from a raw septic tank sludge in a 2 m 3 pilot reactor was investigated, showing that methane concentration increased from 73.15-81.83% upon sonication pretreatment of the sludge [22]. Warade et al [23] designed a portable bioreactor having 35 l working volume for producing biogas from Napier grass along with cow dung at an operating temperature range from 20 to 32 o C. They reported that the biogas production reached as high as 0.44 m 3 /kg VS. By using a compact plug ow reactor, Ramaswamy and Vemareddy [24] could produce biogas from cow dung and water in ratio of 1:10, which was enough to cook three meals a day for a family of six. Zeng et al [25] constructed a self-otation bioreactor and investigated its performance.…”
Section: Introductionmentioning
confidence: 99%